Advances in developing screening methods and improving aluminum resistance in common bean and brachiaria - Rao, Idupulapati M.; Wenzl, Peter; Arango Vélez, Adriana; Miles, John W.; Watanabe, Toshihiro; Shinano, Takuro; Osaki, Mitsuru; Wagatsuma, Tadao; Manrique Carpintero, Germán; Beebe, Stephen E.; Tohme, Joseph M.; Ishitani, Manabu; et al. (2008)
We summarize progress made towards the development of tools and knowledge that aid the genetic improvement of aluminum (Al) resistance in two of CIAT’s (International Center for Tropical Agriculture) commodity crops; common bean (Phaseolus vulgaris L.) and brachiariagrasses (Brachiaria spp. Grisib). Approximately 40% of common bean production is on acid soils where Al toxicity limits root development. Improving Al resistance, therefore, is an important breeding objective. We compared a group of 53 common bean genotypes with differing levels of adaptation to acid soils to identify Al resistant genotypes using a hydroponic screening method. Four different root traits (percent inhibition of root elongation, percent increase of average root diameter, total root length per plant and total number of root tips per plant) were identified as useful indicators for Al resistance. Application of this method to 30 accessions of scarlet runner bean (P. coccineus L.) identified three Al-resistant genotypes that could be used for introgressing Al resistance into cultivated germplasm. Work is in progress to characterize the physiological mechanisms underpinning Al resistance in common bean. This will facilitate developing simplified screening procedures and identifying quantitative trait loci (QTLs) contributing to Al resistance. Compared to common bean, brachiariagrasses tend to be better adapted to acid soils. Yet edaphic adaptation is an important component of CIAT’s and EMBRAPA’s (Empresa Brasiliera de Pesquisa Agropecuária) breeding programs because one of the three parental genotypes is poorly adapted. We developed and incorporated into our breeding program a solution-culture technique that uses rooted stem cuttings to screen for Al resistance and root vigor, both of which are segregating in breeding populations. Physiological research into the remarkably high level of Al resistance of signalgrass (B. decumbens Stapf) has ruled out a significant contribution of organic-acid secretion at root apices (a widespread Al-exclusion mechanism in plants). Instead, Al resistance appears to be a facet of a more generic resistance mechanism that prevents intoxication by inorganic cations, possibly as a result of the change in composition of the lipid bilayer of root cell plasma membranes. Once taken up into roots, Al appears to be complexed by low-molecular-weight ligands such as citrate. Other adaptive traits may counteract secondary effects of Al toxicity on phosphorus (P) nutrition through stimulation of P uptake or use efficiency.